The Description of Dermoscopy and Wood’s Lamp on Melasma - Ryski Meilia Novarina; Rahmadewi Rahmadewi; Hari Sukanto (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Melasma is an acquired hypermelanosis disorder occurred symmetrically on the sun exposure area, predominantly on the face and neck. Melasma classification based on Wood’s light examination does not always have positive correlation with the histopathologic examination. Dermoscopy is a new non-invasive modality for examining melasma. Purpose: To evaluate melasma classification based on dermoscopy and Wood’s lamp examination. Methods: This is a descriptive observational cross sectional study, the subjects are melasma patients in Cosmetic Division of Dermatology and Venereology Outpatient Clinic of Dr. Soetomo hospital. This research was conducted for 2 months with a total of 100 samples that had been performed dermoscopy and Wood’s lamp examinations. Results: Conformity melasma examination results in this study obtained three clinical types of melasma, the vast majority were melasma mixture (72 samples). On dermoscopic examination obtained dermal melasma amount of 17 samples (17%) and telangiectasis structure 38%. In addition dermoscopy can also be used to detect ochronosis on the melasma lesions (7 of 100 samples) with the characteristics are arciform curvilinear (worm-like pattern) and teleangiectasis, dot/globuler bluish brown-black, greyish/bluish brown diffuse amorphic structure, and structureless area. Conclusions: Dermoscopic examination revealed more detailed structure and color of melanin deposit in the superficial dermis, teleangiectasis and early detection of ochronosis. Histopathology still the gold standard diagnosis of melasma and ochronosis lesion.